Two new species of European Stevenia Robineau-Desvoidy (Diptera: Rhinophoridae) and a key to the Palaearctic species - Cerretti, Pierfilippo; Pape, Thomas (Zootaxa, 2007)
Two new species of Stevenia are described from Europe: Stevenia etrusca sp. nov. (Italian mainland: Toscana) and S. palermitana sp. nov. (Italy: Sicily, Palermo prov.). A key to all known Palaearctic species of the genus is provided.